2017
DOI: 10.18203/2320-6012.ijrms20172425
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical outcome in intra articular distal humerus fractures treated with dual plating

Abstract: Background: In adults, distal humerus fractures are uncommon and intra-articular, oftenly involve both the medial and lateral columns. Open reduction and surgical fixation with plating gives good results. The aim of this study is to evaluate clinical outcome in intra articular distal humerus fractures treated with dual plating.Methods: This is a prospective type of study of 20 cases of supra condylar fracture humerus with inter condylar extension treated surgically with dual plating one on the medial boarder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
3
5
2
Order By: Relevance
“…Newer, minimally invasive, percutaneously inserted bridge plates also have been described and have been used to avoid extensive dissection and potential nerve injury [9,10] . In our study, we treated all 20 cases with open reduction and internal fixation with dual plating in 90-90 configuration i. e. one plate on medial boarder and another on posterior surface of lateral column, were 12(60%) males and 8(40%) females comparable to study by Shaik RB et al [1] and in Wang et al [11] studies showed 60% males and 40% females. In which 14 cases (70%) were due to road traffic accident (RTA) and 6 cases (30%) were due to direct fall injury comparable to Henley et al [11] study showed 61% cases due to RTA and 39% cases due to direct injury.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Newer, minimally invasive, percutaneously inserted bridge plates also have been described and have been used to avoid extensive dissection and potential nerve injury [9,10] . In our study, we treated all 20 cases with open reduction and internal fixation with dual plating in 90-90 configuration i. e. one plate on medial boarder and another on posterior surface of lateral column, were 12(60%) males and 8(40%) females comparable to study by Shaik RB et al [1] and in Wang et al [11] studies showed 60% males and 40% females. In which 14 cases (70%) were due to road traffic accident (RTA) and 6 cases (30%) were due to direct fall injury comparable to Henley et al [11] study showed 61% cases due to RTA and 39% cases due to direct injury.…”
Section: Discussionsupporting
confidence: 74%
“…Distal humerus fractures make up 0.5 to 2% of all fractures, but up to 30% of fractures involving the elbow [1] . In adults, most distal humerus fractures are intra-articular and involve both the medial and lateral columns [1] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two (2) patients (10%) had Gustilo type I (all males, one with gunshot and one after road traffic accident). Posterior Campbell's approach was used in fourteen (14) patients (70%) and Trans-olecranon approach was done in Six (6) patients (30%). In Six (6) type C I patients (30%) fractures Osteosynthesis were achieved by Inter-condylar Malleolar screws, one-third tubular plate and reconstruction plate.…”
Section: Resultsmentioning
confidence: 99%